Differential alternative polyadenylation contributes to the developmental divergence between two rice subspecies, japonica and indica. (13th February 2019) - Zhou, Qian; Fu, Haihui; Yang, Dewei; Ye, Congting; Zhu, Sheng; Lin, Juncheng; Ye, Wenbin; Ji, Guoli; Ye, Xinfu; Wu, Xiaohui; Li, Qingshun Quinn
Summary: Alternative polyadenylation (APA) is a widespread post‐transcriptional mechanism that regulates gene expression through mRNA metabolism, playing a pivotal role in modulating phenotypic traits in rice ( Oryza sativa L.). However, little is known about the APA‐mediated regulation underlying the distinct characteristics between two major rice subspecies, indica and japonica . Using a poly(A)‐tag sequencing approach, polyadenylation (poly(A)) site profiles were investigated and compared pairwise from germination to the mature stage between indica and japonica, and extensive differentiation in APA profiles was detected genome‐wide. Genes with subspecies‐specific poly(A) sites were found to contribute to subspecies characteristics, particularly in disease resistance of indica and cold‐stress tolerance of japonica . In most tissues, differential usage of APA sites exhibited an apparent impact on the gene expression profiles between subspecies, and genes with those APA sites were significantly enriched in quantitative trait loci (QTL) related to yield traits, such as spikelet number and 1000‐seed weight. In leaves of the booting stage, APA site‐switching genes displayed global shortening of 3′ untranslated regions with increased expression in indica compared with japonica, and they were overrepresented in the porphyrin and chlorophyll metabolism pathways. This phenomenon may lead to a higher chlorophyll content and photosynthesis in indica than in japonica, being associated with their differential growth rates and yield potentials. We further constructed an online resource for querying and visualizing the poly(A) atlas in these two rice subspecies. Our results suggest that APA may be largely involved in developmental differentiations between two rice subspecies, especially in leaf characteristics and the stress response, broadening our knowledge of the post‐transcriptional genetic basis underlying the divergence of rice traits. Significance Statement: Genome‐wide comparison analysis of alternative polyadenylation (APA) profiles of 14 tissues/developmental stages showed that different usage of poly(A) sites contributed to the divergence of subspecies' characteristics, including leaf chlorophyll content, photosynthesis and stress responses, between two rice subspecies. These findings unveil the APA‐mediated post‐transcriptional regulation mechanism underlying the distinct characteristics of two major rice subspecies, and are important for facilitating future functional studies of APA and rice breeding.